Characterization of drop-casted graphene/cellulose thin film on printing paper substrate - Amirul Hadi Azmi; Shaharin Fadzli Abd Rahman; Mastura Shafinaz Zainal Abidin (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Paper electronics is an emerging technology to implement flexible and wearable electronics devices via ink printing process. This paper evaluates the feasibility of using conventional printing paper for coating process with graphene/cellulose ink. 4 different types of regularly used conventional printing papers were used as substrates in this work. The conductive graphene ink was prepared through exfoliation of graphite in cellulose solution. The paper substrates surface morphology and sheet resistance of the drop-casted conductive ink on each paper were analyzed and discussed. Glossy paper was found to be suitable paper substrate for the printing of the formulated ink due to its low surface roughness of 16 nm. The value of sheet resistance of the graphene/cellulose thin film can be lowered to 4.11 kΩ/sq by applying multiple drops. This work suggests that conventional printing paper may offer solution for highly scalable and low-cost paper electronics.